Multiphase power conversion system with hybrid switching strategy of modulated inverters - Oleschuk, V.; Ermuratskii, V. (Технічна електродинаміка, 2015)
In this paper, two switching strategies have been combined for control of cascaded PWM inverters of dual three-phase adjustable speed drive with asymmetrical induction motor. The presented combined switching techniques allow insuring elimination of common-mode voltages in drive system. Algorithms of synchronized modulation insure symmetries of voltage waveforms of inverters of system for a whole control diapason. Simulations validate performance of systems with combined control strategy of modulated voltage source inverters with low switching frequency.